If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 54 + 15x = 72 + 6x Solving 54 + 15x = 72 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 54 + 15x + -6x = 72 + 6x + -6x Combine like terms: 15x + -6x = 9x 54 + 9x = 72 + 6x + -6x Combine like terms: 6x + -6x = 0 54 + 9x = 72 + 0 54 + 9x = 72 Add '-54' to each side of the equation. 54 + -54 + 9x = 72 + -54 Combine like terms: 54 + -54 = 0 0 + 9x = 72 + -54 9x = 72 + -54 Combine like terms: 72 + -54 = 18 9x = 18 Divide each side by '9'. x = 2 Simplifying x = 2
| 5x+63=12x+35 | | 10x+14=3x+42 | | 5x+90=15x+40 | | 6x+32=24+10x | | 36+14x=63+5x | | 12+10x=18+7x | | 6x+24=9x+6 | | 36+14x=72+5x | | 12+8x=4x+36 | | 8x+42=14x+36 | | 6x+28=16+10x | | 8+7x=10+5x | | 5x+42=12x+14 | | 3x+7+2(3+x)= | | 4x+10=2+6x | | 24+7x=12+10x | | 2x+30=10+7 | | 42+4x=10x+24 | | 3x+7+3(3+x)= | | 20+15x=70+5x | | 66+12x=1x+88 | | 6x+64=14x+48 | | 7x+40=10+12x | | (5/6x)-2x=(5/3)-(8/3) | | 33+14x=55+3x | | 8+3x=4+7x | | 32+13x=5x+48 | | 66+2x=13x+55 | | 18+11x=5x+30 | | 14x+24=2x+72 | | 3x+50=13x+30 | | 42+8x=14x+12 |